The Risks of Innovation : Are Innovating Firms Less Likely to Die? - Fernandes, Ana M.; Paunov, Caroline (MIT Press, 2015)
While innovation matters for competitiveness it may expose firms to survival risks. Using plant-product data for Chile and discrete-time hazard models we show that innovating plants have a lower hazard of exit. However, risk impacts strongly on the innovation-exit relationship: only innovators that retain diversified sources of revenue or face lower market risk are less likely to die. Single-product innovators are at greater risk of exiting. Exposure to technical risk does not affect exit probabilities differentially. We provide tentative evidence that single-product innovators have higher profits which helps to rationalize their innovation decision despite the increased risk of exit.